2017
DOI: 10.1017/qua.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Inland dunes on the abandoned bed of Glacial Lake Chicago indicate eolian activity during the Pleistocene-Holocene transition, southwestern Michigan, USA

Abstract: Inland dune fields have recently emerged as a source of data for reconstructing paleoenvironments and climate in the western Great Lakes region of North America during the Pleistocene-Holocene transition. We employ optically stimulated luminescence (OSL) methods, radiocarbon ages, soils, and landform relationships to determine the age of inland dunes in Ottawa County, Michigan. These dunes rest on the abandoned bed of Glacial Lake Chicago, which is thought to have been exposed after~13.6 ka. OSL analyses from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
(127 reference statements)
0
7
0
Order By: Relevance
“…Large-scale, Late Pleistocene transport of loess on generally westerly winds, out of north-south flowing meltwater river valleys, has long been known for this region and is therefore not shown here. Compiled from Arbogast et al (2015Arbogast et al ( , 2017, Campbell et al (2011), Colgan et al (2017, Hanson et al (2015), Kilibarda and Blockland (2011), Krist and Schaetzl (2001), Loope et al (2004), Rawling et al (2008), Schaetzl et al (2014Schaetzl et al ( , 2016, Stanley andSchaetzl (2011), andVader et al (2012). Black arrows indicate data from dunes, gray arrows indicate data from loess, dashed arrows indicate data from spits or other features.…”
Section: Study Areamentioning
confidence: 99%
“…Large-scale, Late Pleistocene transport of loess on generally westerly winds, out of north-south flowing meltwater river valleys, has long been known for this region and is therefore not shown here. Compiled from Arbogast et al (2015Arbogast et al ( , 2017, Campbell et al (2011), Colgan et al (2017, Hanson et al (2015), Kilibarda and Blockland (2011), Krist and Schaetzl (2001), Loope et al (2004), Rawling et al (2008), Schaetzl et al (2014Schaetzl et al ( , 2016, Stanley andSchaetzl (2011), andVader et al (2012). Black arrows indicate data from dunes, gray arrows indicate data from loess, dashed arrows indicate data from spits or other features.…”
Section: Study Areamentioning
confidence: 99%
“…Broad gray column is Younger Dryas time and narrow gray columns are shorter stadial events. OSL dates from sand dunes at: A) Ottawa County, Michigan (Colgan et al 2017); B) central sand plains of Wisconsin, note error bars are not shown on all samples due to space limitation ; C) Fair Oaks dune field, northwest Indiana (Kilibarda and Blockland 2011); D) Rosco dune field, northern Lower Peninsula of Michigan (Arbogast et al 2015); E) northwest Ohio (Fisher et al 2015); F) northwest Ohio (Campbell et al 2011); G) Mongo dune field (this study). H) Probability density function plot of 59 OSL ages on dunes in B through G. Note shoulder centered on 14 ka (Older Dryas), the main peak towards the end of the Younger Dryas, and a shoulder during the Preboreal.…”
Section: Discussionmentioning
confidence: 81%
“…Dune work along Great Lake coastlines has suggested a relationship between lake level (usually rising) and renewed coastal dune activity covering the past ~5000 years (e.g., Loope and Arbogast 2000;Arbogast et al 2002;Loope et al 2004;Hansen et al 2010;Fisher et al 2012;Baca et al 2014;Hanes et al 2014). The only late glacial age SGLR dune study site along the coast with source sand controlled directly by water level changes is on the glaciolacustrine plain of glacial Lake Chicago in Ottawa County, Michigan (Colgan et al 2017). All other study sites are further inland in Michigan (Arbogast et al 2015;, upwind of Lake Michigan (Rawling et al 2008), or far enough south of Lake Michigan that changes in sediment supply at the coast would not affect the inland dunes in Indiana (Kilibarda and Blockland 2011; this study) or in Ohio (Campbell et al 2011;Fisher et al 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Michael Crosser, president of the International Association of Geomorphologists, said at the opening ceremony that similar geomorphological features exist in the world, but the geomorphology of Zhangjiajie should be recognized by the world because it lacks such distinctive features and scale and integrates aesthetic feeling and scientific research value. Zhangjiajie, a sandstone landform, is very rare in China and even in the world, and its formation conditions are very harsh (Colgan et al, 2017). Therefore, in order to protect the ecological environment of the peak forest landform in Wulingyuan Scenic Area and maintain the integrity and stability of the peak forest landform, it is necessary to study the optimization method of the spatial structure characteristics of the peak forest landform in Wulingyuan Scenic Area.…”
Section: Introductionmentioning
confidence: 99%